A2.6 MTOR plays a decisive role in the mesenchymal tissue response to inflammation in arthritis. (13th February 2015) - Karonitsch, T; Dalwigk, K; Herdy, B; Kandasamy, K; Niederreiter, B; Holinka, J; Sevelda, F; Windhager, R; Bilban, M; Weichhart, T; Saemann, M; Smolen, JS; et al.
Abstract : Accumulating evidence supports the concept that resident mesenchymal cells, namely fibroblast-like synoviocytes (FLS) actively participate in the destructive, inflammatory process of rheumatoid arthritis (RA). FLS maintain a synovial microenvironment that helps to recruit, retain, and activate immune cells, resulting in chronic inflammation with attendant joint destruction. Here, we provide evidence that the mechanistic target of rapamycin (mTOR), which overall has evolved as a major factor for the maintainance of tissue homeostasis and function, is also a critical component of the inflammatory process in synovitis. Immunohistochemical studies revealed that mTOR is activated in rheumatoid synovitis, particularly in FLS of the hyperplastic synovial lining layer. By using western blot or advanced cell biological methods, such as a recently described synovial organ culture system, we further demonstrate that the proinflammatory cytokine TNF positively regulates the mTOR pathway in FLS. To further define the biological significance of these findings, we made use of genome-wide transcriptome analysis. Remarkably, these analyses revealed a so far unknown decisive (modulatory) role for mTOR in the gene expression programs induced by TNF. Thus, inhibition of mTOR by specific inhibitors, such as Torin-1 or PP242, increased the TNF-induced expression of genes, all known to be regulated by NFkB signalling circuit (e.g. PTGS2, IL8, CCL20). By contrast, inhibition of mTOR diminished the TNF-mediated induction of "interferon regulated genes" (IRG), including TNFSF10, CXCL11 and TNFSF13B (BAFF). In conclusion, these studies provide new insight into determinants of the synovial tissue response to inflammation and suggest a multifaceted regulatory role for mTOR in synovial inflammatory processes.